Mechanochemical Synthesis of High Crystalline Cerium Hexaboride Nanoparticles from CeO2‐B2O3‐Mg Ternary System. Issue 4 (5th April 2016) - Torabi, Omid; Naghibi, Sanaz; Golabgir, Mohammad‐Hossein; Jamshidi, Amin
Abstract: High crystalline cerium hexaboride (CeB6 ) nanoparticles (NPs) were synthesized using mixture of mag‐ nesium (Mg), cerium oxide (CeO2 ) and boron oxide (B2 O3 ) via the mechanochemical process at room tem‐ perature. Based on the results, magnesiothermic reduction of B2 O3 occurred after about 2 h of milling in a mechanically induced self‐sustaining reaction (MSR). The significant amount of heat produced by the reduction reaction resulted in CeO2 reduction to elemental Ce which finally reacted with elemental B and formed CeB6 compound. According to XRD analyses, the degree of crystallinity and lattice parameter of the product was calculated about 93 % and 4.1458 Å, respectively. The morphology observations revealed that the synthesized CeB6 had semi‐cubic shape with the range of size 25–60 nm. The synthesis of CeB6 during the thermal treatment was studied by simultaneous thermal analysis (STA) technique. It was found that the reduction of B2 O3 took place after melting of Mg meanwhile, no CeB6 phase achieved even up to 1100 °C. Abstract : High crystalline CeB6 has been synthesized starting with Mg, CeO2 and B2 O3 . MSR mode reaction took place after 2 h milling. Mg reduced B2 O3 and produced a significant amount of heat which promoted the reduction of CeO2 . Decrease in B2 O3 value changed the mechanochemical behavior from MSR to progressive reaction. The leached sample after 4 h milling contains 30–60 nm semi‐cubic particles.